2020
DOI: 10.1007/s40688-020-00328-3
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study Exploration into the Benefits of Teaching Self-Care to School Psychology Graduate Students

Abstract: It has long been established that school psychology practitioners experience high levels of burnout. As a means of preventing burnout among future practitioners, school psychology training programs are frequently encouraged to teach and model self-care to students. This is particularly important as the current generation of graduate students experience high levels of anxiety and depression, but there have been very few examples in the research literature of how training programs should teach self-care and whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Recent literature by Daly and Gardner (2022) explored the benefits of teaching self-care to school psychology graduates with a small sample ( N = 22) and found that students’ reflections of self-care activities assisted in meeting the demands associated with their graduate training. However, the authors recommend further examination of this finding with a larger sample size.…”
Section: School Psychologists’ Self-carementioning
confidence: 99%
See 3 more Smart Citations
“…Recent literature by Daly and Gardner (2022) explored the benefits of teaching self-care to school psychology graduates with a small sample ( N = 22) and found that students’ reflections of self-care activities assisted in meeting the demands associated with their graduate training. However, the authors recommend further examination of this finding with a larger sample size.…”
Section: School Psychologists’ Self-carementioning
confidence: 99%
“…It is particularly important to address school psychologists’ self-care as research (Huebner, 1993; Newman, 2013) has indicated that school psychologists, in comparison to clinical, and counseling psychologists, are more susceptible to burnout, due to higher levels of emotional exhaustion (i.e., feeling overwhelmed by job demands), depersonalization (i.e., developing negative attitudes toward clients), decreased levels of personal accomplishment (i.e., feeling incompetent and ill-equipped to support clients), lack of experience, and increased interpersonal relationships (Badali & Habra, 2003; Daly & Gardner, 2022). These findings could be attributed to the vast array of challenges and expectations school psychologists are faced with daily (Fagan & Wise, 2000).…”
Section: School Psychologists’ Self-carementioning
confidence: 99%
See 2 more Smart Citations